FISHBURNE's METHOD AND THE CLASSICAL METHOD OF PHARMACOECONOMIC ANALYSIS IN THE EVALUATION OF ANTIBIOTIC TREATMENT OF ACUTE AND RECURRENT BRONCHITIS IN CHILDREN - Zhukova, Olga V.; Konyshkina, Tatjana M.; Kononova, Svetlana V. (International Journal of Pharmacy and Pharmaceutical Sciences, 2015)
Objective: This study was performed in order to estimate clinical effectiveness of antibiotic therapy in acute and recurrent obstructive bronchitis. For estimation the following was used: the Fishbern method of antibiotics distribution according to clinical effectiveness levels with the help of weighted coefficients and classical costâ€“efficiencyâ€ pharmacoeconomic analysis of the given antibiotic therapy. Then, for the first time ever, the obtained results of both methods were combined. Methods: Materials were presented by the data on antibiotic therapy, given for patients who were hospitalized to the in-patient medical facilities due to acute or recurrent obstructive bronchitis. Medical records of 2 259 patients were included in the study. The patients were 0 to 18 y old. In order to determine the weighed coefficients of each used antibiotic with subsequent distribution according to the levels of clinical effectiveness the Fishbern method was applied. Three levels of clinical effectiveness were used in this study, i.e. high, medium and low. The costâ€“efficiencyâ€ pharmacoeconomic analysis was applied to combine costs and efficiency of the compared therapy courses in acute and recurrent obstructive bronchitis. Results: Finally we found out that the highest probability of positive effect of cephalosporins group agents was associated with the use of Cefotaximum. (Biosynthesis). From the pharmacoeconomic point of view the most effective in treating acute and recurrent obstructive bronchitis in children in the in-patient facilities was Ceftriaxonum (Synthesis). Out of protected penicillins group, we used Amoxicillin/clavulanic acidâ€“original drug Augmentin (Smithkline Beecham Pharmaceuticals) and generic drug Amoxiclav (Lek d. d). Augmentin effectiveness was 0.591, and Amoxiclav effectivenessâ€“0.530. Cost of Augmentin treatment course was 106.26 rub. (1.68 US$), cost of Amoxiclav treatment courseâ€“103.50 rub.(1.63 US$). Augmentin use turned out to be the most reasonable. Augmentin treatment course was characterized by lower ICER coefficient versus Amoxiclav. We found out that from the pharmacoeconomic point of view Azitromicin (Vertex Ltd.) treatment turned out to be the most reasonable of the whole macrolides antibiotics for treatment of acute and recurrent obstructive bronchitis. However, according to the Fishbern clinical effectiveness classification this antibiotic belonged to the group with medium effectiveness level. The group with high effectiveness level included Sumamed, Azitral, Hemomicin, Clacid, Zitrocin and Clabax. Clacid and Clabax were excluded during the pharmacoeconomic analysis. The highest value of ICER coefficient was obtained for Sumamed and made up 39,367.50 rub. (621.53 US$). The highest level of clinical effectiveness was characteristic for Sumamed as well. Besides Sumamed was an original drug of azitromicin. According to the obtained data Azitral and Hemomicin had the lowest values of ICER coefficient (1151.67 rub. (18.18 US$) and 1812.22 rub. (28.61 US$) respectively). Therefore based on the clinical economic analysis these medical agents turned out to be the most suitable. Conclusion: The results of the pharmacoeconomic analysis showed that the most effective drugs in treatment of acute and recurrent obstructive bronchitis in children in in-patient facilities appeared to be the following: out of cephalosporins-Ceftriaxonum (Synthesis), out of protected penicillins-Augmentin (Smithkline Beecham Pharmaceuticals), out of macrolides-Azitromicin (Vertex Ltd.). According to the Fishbern classification, these drugs belonged to the group with medium level of effectiveness. Â 